EVALUATION OF THE YIELD PRODUCTION OF C3 (TRITICUM AESTIVUM L.) AND C4 (ZEA MAYS L.) CEREALS WITH A NEW PLANT PHYSIOLOGICAL PARAMETER - Péter Pepó; Enikő Vári (Journal of Animal and Plant Sciences, 2016)
In a polifactorial long-term experiment, the effects of the year and the agrotechnical factors on the yields and plant physiological parameters (LAI, SPAD) of winter wheat and maize were studied on chernozem soil in the period of 2011-2013. Results of our long-term experiments proved that the yield of winter wheat was influenced both by the fertilization and the crop rotation. The productivity of the C4-type maize was higher than that of the C3-type winter wheat. Our results proved that the plant physiological parameters (LAI, SPAD) of winter wheat (C3) and maize (C4) were not different, however, there were great differences in productivity between the two crops. A new parameter (Ph.C.) was developed for the characterization of the photosynthetic capacity in winter wheat and maize. The Ph.C. values of winter wheat (C3) and maize (C4) were significantly different (300-400 Ph.C. and 800-1200 Ph.C.). The Ph.C. values can also be well used for the characterization of the agrotechnical elements (fertilization, crop rotation, irrigation). A close correlation was found between the yields of maize and winter wheat and the Ph.C. values (r = 0.671-0.938**, r = 0.792-0.934**).
Keywords: C3 (wheat); C4 (maize); photosynthetic capacity (Ph.C.); yield